2021
DOI: 10.1186/s13756-021-00963-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of mobile colistin resistance genes (mcr-3 and mcr-5) in river and storm water in regions of the Western Cape of South Africa

Abstract: Background Colistin is regarded as a last-resort antimicrobial against multi-drug resistant Gram-negative bacteria (GNB), therefore the dissemination of colistin resistance in the environment is of great concern. Horizontal transfer of mobile colistin resistance (mcr) genes to potential pathogens poses a serious problem. This study aimed to describe the presence of colistin resistant GNB and mcr genes in river and storm water in regions of the Western Cape. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…We found that four E.coli B-strains, BL21, BL21D, T7, and Shuffle are intrinsically resistant to colistin with MICs of 8-16 μg/mL. This observation was surprising, as previous studies have used B-strains like BL21D and Shuffle to report MIC values for mcr variants and indicated that the strains were susceptible to colistin (26,30,31). However, our findings are consistent with studies by Trent et al (38) and Xu et al (37), who reported that B-strains BLR(DE3) (obtained from Novagen) and BL21(DE3) (obtained from both Novagen and Stratagene), used in their respective studies, were resistant to colistin.…”
Section: Commonly Used Heterologous Expression Hosts (Ie E Coli B-str...mentioning
confidence: 75%
See 1 more Smart Citation
“…We found that four E.coli B-strains, BL21, BL21D, T7, and Shuffle are intrinsically resistant to colistin with MICs of 8-16 μg/mL. This observation was surprising, as previous studies have used B-strains like BL21D and Shuffle to report MIC values for mcr variants and indicated that the strains were susceptible to colistin (26,30,31). However, our findings are consistent with studies by Trent et al (38) and Xu et al (37), who reported that B-strains BLR(DE3) (obtained from Novagen) and BL21(DE3) (obtained from both Novagen and Stratagene), used in their respective studies, were resistant to colistin.…”
Section: Commonly Used Heterologous Expression Hosts (Ie E Coli B-str...mentioning
confidence: 75%
“…To determine whether a given gene confers colistin resistance and to assess the level of colistin resistance conferred by a given variant or sub-variant, authors oftentimes express mcr genes in heterologous laboratory E. coli strains using either the native plasmid (18, 28, 29) or cloning the gene into a plasmid downstream of an inducible promoter like the T7 RNA polymerase promoter with the lac operator (e.g., pET plasmids) (30, 31). This method is necessary when discovering new variants from whole genome sequence (WGS) data or when the isolate is not available or culturable.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the current study detected high prevalence of ESBL encoding genes in Salmonella isolates. The significance of detecting β-lactamase resistance genes raises public health concerns by limiting the therapeutic choices for treating salmonellosis in animals and humans [47], and COL raises major health concerns, as it is used as a treatment of last resort [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotic resistance against colistin (COL), is becoming more common and a point of concern because it is a last-resort antibiotic used against difficult-to-treat pathogens such as Acinetobacter baumanni, Klebsiella pneumoniae, and Pseudomonas aeruginosa [15][16][17][18][19][20]. Although COL use in humans is uncommon in Africa, it is widely used in livestock [16,19].…”
Section: Introductionmentioning
confidence: 99%
“…Colistin minimum inhibitory concentration (MIC) data were collected from the literature as follows (Supplementary Table S8) (Di Pilato et al, 2016; Liu et al, 2016; Xavier et al, 2016; AbuOun et al, 2017; Borowiak et al, 2017; Carattoli et al, 2017; Ling et al, 2017; Liu et al, 2017; Lu et al, 2017; Poirel et al, 2017; Tijet et al, 2017; Yang et al, 2017; Yin et al, 2017; Zhao et al, 2017; Alba et al, 2018; Carattoli et al, 2018; Chavda et al, 2018; Dortet et al, 2018; Duggett et al, 2018; Eichhorn et al, 2018; Fernandes et al, 2018; Garcia-Graells et al, 2018; Hammerl et al, 2018; Kieffer et al, 2018; Li et al, 2018; Liu et al, 2018; Poirel et al, 2018; Rebelo et al, 2018; Shen et al, 2018; Teo et al, 2018; Wang et al, 2018b; Wang et al, 2018c; Wise et al, 2018; Xiang et al, 2018; Xu et al, 2018b; Xu et al, 2018c; Yang et al, 2018; Abdul Momin et al, 2019; Bitar et al, 2019; Chavda et al, 2019; Cui et al, 2019; Deshpande et al, 2019; Hadjadj et al, 2019; Li et al, 2019; Long et al, 2019; Wang et al, 2019; Yang et al, 2019; Yuan et al, 2019; Zhang et al, 2019; Zheng et al, 2019; Bitar et al, 2020; Cha et al, 2020; Fan et al, 2020; Garcia-Menino et al, 2020; Hatrongjit et al, 2020; Lei et al, 2020; Martins-Sorenson et al, 2020; Neumann et al, 2020; Ngbede et al, 2020; Wang et al, 2020; Anyanwu et al, 2021; Hu et al, 2021; Khanawapee et al, 2021; Leangapichart et al, 2021; Snyman et al, 2021; Stosic et al, 2021; Uddin et al, 2021; Yu et al, 2021). A search of NCBI’s PubMed database (…”
Section: Methodsmentioning
confidence: 99%